The emerging role of snoRNAs in human disease - Xinhai Zhang; Chenglong Wang; Shujun Xia; Fei Xiao; Jianping Peng; Yuxuan Gao; Fengbin Yu; Chuandong Wang; Xiaodong Chen (Genes and Diseases, 2023)
Small nucleolar RNAs (snoRNAs) play critical roles in various biological processes. The aberrant expression or depletion of snoRNAs is related to various diseases. In previous research, most of the snoRNAs were categorized as C/D box snoRNAs and H/ACA box snoRNAs, whose typical functions were thought of as regulation of 2′-O-ribose methylation and pseudouridylation of ribosome RNAs, respectively. However, in the past two decades, studies have revealed an increasing number of snoRNAs without specific targets or determined cell functions. These findings indicated that some potential roles of snoRNAs are still unknown. Numerous studies have indicated the correlation of snoRNAs with human diseases. SnoRNAs play various roles in abundant biological processes, and they have great potential in controlling human diseases. This new and rising field could benefit from investigations of the disease pathogenesis, biomarker identification, and the determination of novel therapeutic targets. This review summarized the reports on snoRNAs and the regulation of different diseases in recent years.